Responder
1. **First Equation:** No real solution.
2. **Second Equation:** \( x = \frac{3 - \sqrt{21}}{2} \) or \( x = \frac{3 + \sqrt{21}}{2} \).
3. **Third Inequality:** \( x < -\frac{3}{2} \) or \( x > 1 \).
4. **Values of \( x \) and \( y \):** \( (3, -3) \) and \( \left(\frac{2}{3}, \frac{5}{3}\right) \).
5. **Expression Value:** \( 1000000000001 \).
6. **Fourth Equation:** No real roots.
Solución
Calculate the value by following steps:
- step0: Calculate:
\(\frac{\left(999999999999^{2}-4\right)}{\left(999999999999-2\right)}\)
- step1: Remove the parentheses:
\(\frac{999999999999^{2}-4}{999999999999-2}\)
- step2: Subtract the numbers:
\(\frac{999999999999^{2}-4}{999999999997}\)
Solve the equation \( \frac{x^{4}+1}{x^{4}}=\frac{1}{2} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{x^{4}+1}{x^{4}}=\frac{1}{2}\)
- step1: Cross multiply:
\(\left(x^{4}+1\right)\times 2=x^{4}\)
- step2: Simplify the equation:
\(2\left(x^{4}+1\right)=x^{4}\)
- step3: Expand the expression:
\(2x^{4}+2=x^{4}\)
- step4: Move the expression to the left side:
\(2x^{4}+2-x^{4}=0\)
- step5: Subtract the terms:
\(x^{4}+2=0\)
- step6: Move the constant to the right side:
\(x^{4}=0-2\)
- step7: Remove 0:
\(x^{4}=-2\)
- step8: The statement is false for any value of \(x:\)
\(x \notin \mathbb{R}\)
Solve the equation \( x(3-x)=-3 \).
Solve the quadratic equation by following steps:
- step0: Solve using the quadratic formula:
\(x\left(3-x\right)=-3\)
- step1: Expand the expression:
\(3x-x^{2}=-3\)
- step2: Move the expression to the left side:
\(3x-x^{2}+3=0\)
- step3: Rewrite in standard form:
\(-x^{2}+3x+3=0\)
- step4: Multiply both sides:
\(x^{2}-3x-3=0\)
- step5: Solve using the quadratic formula:
\(x=\frac{3\pm \sqrt{\left(-3\right)^{2}-4\left(-3\right)}}{2}\)
- step6: Simplify the expression:
\(x=\frac{3\pm \sqrt{21}}{2}\)
- step7: Separate into possible cases:
\(\begin{align}&x=\frac{3+\sqrt{21}}{2}\\&x=\frac{3-\sqrt{21}}{2}\end{align}\)
- step8: Rewrite:
\(x_{1}=\frac{3-\sqrt{21}}{2},x_{2}=\frac{3+\sqrt{21}}{2}\)
Solve the equation \( 111 x^{2}=5 x-4 \).
Solve the equation(The complex numbers system) by following steps:
- step0: Solve using the quadratic formula in the complex numbers system:
\(111x^{2}=5x-4\)
- step1: Move the expression to the left side:
\(111x^{2}-5x+4=0\)
- step2: Solve using the quadratic formula:
\(x=\frac{5\pm \sqrt{\left(-5\right)^{2}-4\times 111\times 4}}{2\times 111}\)
- step3: Simplify the expression:
\(x=\frac{5\pm \sqrt{\left(-5\right)^{2}-4\times 111\times 4}}{222}\)
- step4: Simplify the expression:
\(x=\frac{5\pm \sqrt{-1751}}{222}\)
- step5: Simplify the expression:
\(x=\frac{5\pm \sqrt{1751}\times i}{222}\)
- step6: Separate into possible cases:
\(\begin{align}&x=\frac{5+\sqrt{1751}\times i}{222}\\&x=\frac{5-\sqrt{1751}\times i}{222}\end{align}\)
- step7: Simplify the expression:
\(\begin{align}&x=\frac{5}{222}+\frac{\sqrt{1751}}{222}i\\&x=\frac{5-\sqrt{1751}\times i}{222}\end{align}\)
- step8: Simplify the expression:
\(\begin{align}&x=\frac{5}{222}+\frac{\sqrt{1751}}{222}i\\&x=\frac{5}{222}-\frac{\sqrt{1751}}{222}i\end{align}\)
- step9: Rewrite:
\(x_{1}=\frac{5}{222}-\frac{\sqrt{1751}}{222}i,x_{2}=\frac{5}{222}+\frac{\sqrt{1751}}{222}i\)
- step10: Remove the complex number(s):
\(\textrm{No real solution}\)
Solve the equation \( 3-x<2 x^{2} \).
Solve the inequality by following steps:
- step0: Solve the inequality by testing the values in the interval:
\(3-x<2x^{2}\)
- step1: Move the expression to the left side:
\(3-x-2x^{2}<0\)
- step2: Rewrite the expression:
\(3-x-2x^{2}=0\)
- step3: Factor the expression:
\(\left(1-x\right)\left(3+2x\right)=0\)
- step4: Separate into possible cases:
\(\begin{align}&1-x=0\\&3+2x=0\end{align}\)
- step5: Solve the equation:
\(\begin{align}&x=1\\&x=-\frac{3}{2}\end{align}\)
- step6: Determine the test intervals:
\(\begin{align}&x<-\frac{3}{2}\\&-\frac{3}{2}1\end{align}\)
- step7: Choose a value:
\(\begin{align}&x_{1}=-3\\&x_{2}=0\\&x_{3}=2\end{align}\)
- step8: Test the chosen value:
\(\begin{align}&x<-\frac{3}{2}\textrm{ }\textrm{is the solution}\\&-\frac{3}{2}1\textrm{ }\textrm{is the solution}\end{align}\)
- step9: The final solution is \(x \in \left(-\infty,-\frac{3}{2}\right)\cup \left(1,+\infty\right):\)
\(x \in \left(-\infty,-\frac{3}{2}\right)\cup \left(1,+\infty\right)\)
Solve the system of equations \( 2 x+y=3;x^{2}+y+x=y^{2} \).
Solve the system of equations by following steps:
- step0: Solve using the substitution method:
\(\left\{ \begin{array}{l}2x+y=3\\x^{2}+y+x=y^{2}\end{array}\right.\)
- step1: Solve the equation:
\(\left\{ \begin{array}{l}y=3-2x\\x^{2}+y+x=y^{2}\end{array}\right.\)
- step2: Substitute the value of \(y:\)
\(x^{2}+3-2x+x=\left(3-2x\right)^{2}\)
- step3: Add the terms:
\(x^{2}+3-x=\left(3-2x\right)^{2}\)
- step4: Expand the expression:
\(x^{2}+3-x=9-12x+4x^{2}\)
- step5: Move the expression to the left side:
\(x^{2}+3-x-\left(9-12x+4x^{2}\right)=0\)
- step6: Calculate:
\(-3x^{2}-6+11x=0\)
- step7: Factor the expression:
\(\left(-x+3\right)\left(3x-2\right)=0\)
- step8: Separate into possible cases:
\(\begin{align}&-x+3=0\\&3x-2=0\end{align}\)
- step9: Solve the equation:
\(\begin{align}&x=3\\&x=\frac{2}{3}\end{align}\)
- step10: Calculate:
\(x=3\cup x=\frac{2}{3}\)
- step11: Rearrange the terms:
\(\left\{ \begin{array}{l}x=3\\y=3-2x\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{3}\\y=3-2x\end{array}\right.\)
- step12: Calculate:
\(\left\{ \begin{array}{l}x=3\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{3}\\y=\frac{5}{3}\end{array}\right.\)
- step13: Check the solution:
\(\left\{ \begin{array}{l}x=3\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2}{3}\\y=\frac{5}{3}\end{array}\right.\)
- step14: Rewrite:
\(\left(x,y\right) = \left(3,-3\right)\cup \left(x,y\right) = \left(\frac{2}{3},\frac{5}{3}\right)\)
Let's solve the problems step by step.
### Problem 1: Solve for \( x \)
1. **Equation:** \( 111 x^{2} = 5 x - 4 \)
Rearranging gives us:
\[
111 x^{2} - 5 x + 4 = 0
\]
This quadratic equation has no real solutions.
2. **Equation:** \( x(3-x) = -3 \)
Rearranging gives us:
\[
x^2 - 3x - 3 = 0
\]
Using the quadratic formula, we find:
\[
x_{1} = \frac{3 - \sqrt{21}}{2}, \quad x_{2} = \frac{3 + \sqrt{21}}{2}
\]
3. **Inequality:** \( 3 - x < 2 x^{2} \)
Rearranging gives us:
\[
2 x^{2} + x - 3 > 0
\]
The solution set is:
\[
x \in (-\infty, -\frac{3}{2}) \cup (1, +\infty)
\]
### Problem 2: Determine values of \( x \) and \( y \)
Given the equations:
\[
\begin{align*}
2x + y &= 3 \\
x^{2} + y + x &= y^{2}
\end{align*}
\]
We can solve this system of equations. The solutions are:
\[
(x, y) = (3, -3) \cup (x, y) = \left(\frac{2}{3}, \frac{5}{3}\right)
\]
In decimal form, this is:
\[
(x, y) = (3, -3) \cup (x, y) = (0.67, 1.67)
\]
### Problem 3: Calculate \( \frac{x^{2}-4}{x-2} \)
Given \( x = 999999999999 \):
\[
\frac{x^{2}-4}{x-2} = \frac{999999999999^{2}-4}{999999999997}
\]
This expression simplifies to:
\[
999999999999 + 2 = 1000000000001
\]
### Problem 4: Explain why \( \frac{x^{4}+1}{x^{4}}=\frac{1}{2} \) has no real roots
Rearranging gives:
\[
x^{4} + 1 = \frac{1}{2} x^{4}
\]
This simplifies to:
\[
\frac{1}{2} x^{4} + 1 = 0
\]
Since \( x^{4} \) is always non-negative, \( \frac{1}{2} x^{4} + 1 \) is always positive. Therefore, there are no real solutions to this equation.
### Summary of Results
1. **First equation:** No real solution.
2. **Second equation:** \( x_{1} = \frac{3 - \sqrt{21}}{2}, x_{2} = \frac{3 + \sqrt{21}}{2} \).
3. **Third inequality:** \( x \in (-\infty, -\frac{3}{2}) \cup (1, +\infty) \).
4. **Values of \( x \) and \( y \):** \( (3, -3) \cup \left(\frac{2}{3}, \frac{5}{3}\right) \).
5. **Value of expression:** \( 1000000000001 \).
6. **Fourth equation:** No real roots.
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución